Peas, natural resources for a sustainable future: a multifaceted review of nutritional, health, environmental, and market perspectives - Ćujić Nikolić, Nada; Mutavski, Zorana; Šavikin, Katarina; Živković, Jelena; Pavlović, Suzana; Jones, Petra; Copperstone, Claire; Can Aytar, Erdi; Aydin, Betül; Van Bavegem, Evelien; Kunili, Ibrahim Ender; Özmen, Özge; et al. (Frontiers in Nutrition, 2026)
The pea (Pisum sativum L.) is an emerging pillar in plant-based nutrition and sustainable food systems due to its high-quality proteins, diverse bioactive compounds, and agroecological benefits. This review provides an updated synthesis of the nutritional composition, health-promoting properties, and environmental relevance of peas, emphasizing recent scientific findings. Pea seeds typically contain 20%−40% protein, 45%−55% starch, and 10%−15% dietary fiber, alongside essential micronutrients such as vitamin C (40–60 mg/100 g), folate (60–70 μg/100 g), vitamin K (30–45 μg/100 g), iron (1.5–2.0 mg/100 g), and manganese (0.4–0.6 mg/100 g). Their storage proteins, primarily legumin and vicilin, offer high digestibility and amino acid profiles compatible with human requirements, supporting their rapidly growing use in protein isolates and meat- and dairy-alternative products. Peas represent a valuable source of phenolic acids, flavonoids, and saponins, which contribute to notable antioxidant (50–120 μmol Trolox/g) and anti-inflammatory activities demonstrated in preclinical studies. Compared with other legumes, peas exhibit a lower glycemic index (35–45), making them suitable for metabolic health applications. Agronomically, pea cultivation enhances soil fertility through biological nitrogen fixation (up to 150 kg N/ha), supporting reduced fertilizer inputs and improved crop rotation performance, aligning with circular economy and climate-resilience strategies. Despite these advantages, global consumption and breeding innovation remain insufficient to meet the rising demand for alternative proteins. Future opportunities include improving protein extraction technologies, valorizing processing side-streams, and exploring underutilized phytochemicals to strengthen the nutritional and sustainability profile of pea-based food systems.